Tick innate immunity - Kopácek, Petr; Hajdusek, Ondrej; Buresová, Veronika; Daffre, Sirlei (Advances in experimental medicine and biology, 2010)
Ticks are blood feeding parasites transmitting a wide variety of pathogens to their vertebrate hosts. The vector competence of ticks is tightly linked with their immune system. Despite its importance, our knowledge of tick innate immunity is still inadequate and the limited number of sufficiently characterized immune molecules and cellular reactions are dispersed across numerous tick species. The phagocytosis of microbes by tick hemocytes seems to be coupled with a primitive complement-like system, which possibly involves self/nonself recognition by fibrinogen-related lectins and the action of thioester-containing proteins. Ticks do not seem to possess a pro-phenoloxidase system leading to melanization and also coagulation of tick hemolymph has not been experimentally proven. They are capable of defending themselves against microbial infection with a variety of antimicrobial peptides comprising lysozymes, defensins and molecules not found in other invertebrates. Virtually nothing is known about the signaling cascades involved in the regulation of tick antimicrobial immune responses. Midgut immunity is apparently the decisive factor of tick vector competence. The gut content is a hostile environment for ingested microbes, which is mainly due to the antimicrobial activity of hemoglobin fragments generated by the digestion of the host blood as well as other antimicrobial peptides. Reactive oxygen species possibly also play an important role in the tick-pathogen interaction. The recent release of the Ixodes scapularis genome and the feasibility of RNA interference in ticks promise imminent and substantial progress in tick innate immunity research.
Keywords: Immunity, Innate; přirozená imunita; Hemocytes; Host-Pathogen Interactions; Ticks; klíšťata; Animals; hemocyty; interakce hostitele a patogenu; zvířata